Interrogating Epistemic Internalism and Externalism within the Framework of Integrative Humanism - Uzoigwe, Elias Ifeanyi E. (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2020)
Internalism and externalism are theories discussed in moral philosophy, philosophy of mind, sociology, economics, and some other disciplines within the humanities, hence the prefix “epistemic”. Epistemologists of diverse schools of thought and orientations have discussed internalism and externalism from the purview of the Gettier problem, reliabilism, naturalised epistemology and, in fact, the issue of justification in general. They all deserve appreciation for their noble inputs towards expanding the horizon of epistemic discourse. It has been argued by Steve that internalism and externalism are contemporary issues in epistemology that have nothing to do with either the classical, medieval or contemporary epochs of philosophical inquiry. This work strongly holds a contrary view, because every epistemic theory or concept proximately or remotely has something that ties it together with the already existing ones. No epistemic theory has ever held sway without reference to other already existing theories either as a critique, a criticism, an appraisal, or a review. The primary concern of this research is to have a shot at internalism and externalism as a contemporary advancement of rationalism and empiricism and then systematise the ideas within the purview of integrative humanism. It is with this mindset of epistemic harmonisation that ratio-internalist and empirico-externalist spirito-centrism is made possible. This understanding of our epistemic folkways is construed as a new way of grappling with the missing link between rationalism and internalism and between empiricism and externalism - all deriving a new impetus in the light of the integrativist approach to knowledge.